POST-MATERIALISM IN THE US TO THE ACCEPTANCE OF RELIGIOUS LGBTQ+ IN NEW MEDIA - Marhamah, Annida Ul (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This research explores the interaction between traditional and postmaterialist values, focusing on how personal growth, self-expression, and identity formation have challenged long-standing societal norms. Drawing on Ronald Inglehart’s post-materialism theory and Judith Butler’s theory of queer theory, this paper investigates how religious LGBTQ+ individuals—often referred to as “Religious Queer”—have attempted to assert their identity representations within religious communities and public media. Their presence in New Media has prompted several reactions, some strong and some supportive, as it disrupts conventional associations between religiosity and heteronormativity, challenging long-held norms, producing critical conversations, and inviting broader acceptance of diverse identities within spiritual and digital spaces. Through qualitative research, this paper examines how religious queer individuals deconstruct inherited interpretations of religion and assert that their gender and sexuality are not inherently incompatible with their faith. Therefore, this study explores how the intersection of postmaterialist values and queer identities enables a reimagining of religious belief and personal authenticity in New Media.